Effects of juvenile hormone in fertility and fertility-signaling in workers of the common wasp Vespula vulgaris. - Cintia Akemi Oi; Helena Mendes Ferreira; Rafael Carvalho da Silva; Andreas Bienstman; Fabio Santos do Nascimento; Tom Wenseleers (PLoS ONE, 2021)
In the highly eusocial wasp, Vespula vulgaris, queens produce honest signals to alert their subordinate workers of their fertility status, and therefore they are reproductively suppressed and help in the colony. The honesty of the queen signals is likely maintained due to hormonal regulation, which affects fertility and fertility cue expression. Here, we tested if hormonal pleiotropy could support the hypothesis that juvenile hormone controls fertility and fertility signaling in workers. In addition, we aimed to check oocyte size as a proxy of fertility. To do that, we treated V. vulgaris workers with synthetic versions of juvenile hormone (JH) analogue and a JH inhibitor, methoprene and precocene, respectively. We dissected the treated females to check ovary activation and analyzed their chemical profile. Our results showed that juvenile hormone has an influence on the abundance of fertility linked compounds produced by workers, and it also showed to increase oocyte size in workers. Our results corroborate the hypothesis that juvenile hormone controls fertility and fertility signaling in workers, whereby workers are unable to reproduce without alerting other colony members of their fertility. This provides supports the hypothesis that hormonal pleiotropy contributes to keeping the queen fertility signals honest.